Nrf2 and NF‐қB interplay in tamoxifen‐induced hepatic toxicity: A promising therapeutic approach of sildenafil and low‐dose γ radiation. Issue 5 (30th January 2023) - Karam, Heba M.; Galal, Shereen M.; Lotfy, Dina M.
Abstract: Tamoxifen‐induced hepatotoxicity is an inevitable side effect during breast cancer treatment. Low‐dose gamma irradiation (IRR) shows many beneficial effects by stimulating various biological processes. This study evaluates the possible effect of sildenafil and low‐dose gamma radiation on liver damages as new treatment strategies. Group I (control), group II: (tamoxifen), group III: (tamoxifen + Sildenafil), group IV: (tamoxifen+ irradiation) and group V: (tamoxifen +Sildenafil + irradiation). Rats were sacrificed after 5 h from tamoxifen injection. Results showed that tamoxifen caused elevation in serum AST, ALT and ALP as well hepatic ROS, iNOS, MDA, Keap‐1 and NF‐Kb, in addition to diminution in hepatic Nrf2 and HO‐1. Exposure to low‐dose gamma radiation and sildenafil amended the alterations in the measured parameters in serum and tissue. Moreover, all results were confirmed by histopathological examination. In conclusion, sildenafil and low‐dose gamma radiation can mitigate the toxicity induced by tamoxifen in liver tissues. Hence, this treatment could be further evaluated as a new approach for alleviating various liver disorders.